Artificial disasters: some remarks on water and warfare in the Middle Ages (Studi di storia medioevale e di diplomatica - Nuova Serie, 2022)
This paper focuses on a particular aspect of medieval warfare: the artificial use of water to cause flooding for tactical purposes or devastation. Particular attention is paid to the factors that made the use of these techniques possible; to the context in which they were used; to the personnel involved in the implementation of these hydraulic enterprises.
Keywords: Middle Ages; Northern Italy; water; floods; warfare; strategy